Analysis of the Effect of Investment, Inflation, Credit Interest Rates, Exchange Rates on Mineral Fuel Exports in Central Kalimantan Province - Lenni Katarina Siregar (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
The purpose of this study is to analyze the effect of investment, inflation, interest rates, exchange rates on mineral fuel exports in Central Kalimantan Province partially or simultaneously. This type of research is quantitative research using multiple linear regression analysis tools. The results of this study indicate that simultaneously investment, inflation, interest rates, exchange rates have an effect on mineral fuel exports in Central Kalimantan Province. Partially, investment and exchange rate have a significant effect on mineral fuel exports. Meanwhile, interest rates and inflation do not have a significant effect on fuel exports in the province of Central Kalimantan.